Adaptive airbag system for increased evacuation safety. (1st November 2022) - Faraj, Rami; Popławski, Błażej; Gabryel, Dorian; Kowalski, Tomasz; Hinc, Krzysztof
Highlights: The novel adaptive airbag system for people evacuation is investigated. Experimentally validated numerical models are applied for optimization analyses. The original adaptation method is proposed based on statistical real-life study. The possibility of a significant reduction of impact loading is demonstrated. Abstract: This short communication is aimed at indication of a significant problem to be solved by researchers working in the field of engineering structures. The contribution concerns a very important application of a rescue cushion, which is an airbag system devoted to the impact mitigation appearing during evacuation of people from heights. Although, a very similar in the principle of their operation, car airbags have been thoroughly tested, rescue cushions have not received sufficient attention. It should be emphasized that the performance of the actually operated devices is far from sufficient and even fatal accidents occur. The authors identified the problem and have initiated a study, which includes numerical simulation and experimental validation of the impact absorption process, as well as the elaboration of a suitable adaptive solution.